Preliminary Outcomes of Combined Treadmill and Overground High-Intensity Interval Training in Ambulatory Chronic Stroke - Boyne, Pierce; Doren, Sarah; Scholl, Victoria; Staggs, Emily; Whitesel, Dustyn; Carl, Daniel; Shatz, Rhonna; Sawyer, Russell; Awosika, Oluwole O.; Reisman, Darcy S.; Billinger, Sandra A.; Kissela, Brett; et al. (Frontiers in Neurology, 2022)
Purpose: Locomotor high-intensity interval training (HIIT) is a promising intervention for stroke rehabilitation. However, overground translation of treadmill speed gains has been somewhat limited, some important outcomes have not been tested and baseline response predictors are poorly understood. This pilot study aimed to guide future research by assessing preliminary outcomes of combined overground and treadmill HIIT. Materials and Methods: Ten participants >6 months post-stroke were assessed before and after a 4-week no-intervention control phase and a 4-week treatment phase involving 12 sessions of overground and treadmill HIIT. Results: Overground and treadmill gait function both improved during the treatment phase relative to the control phase, with overground speed changes averaging 61% of treadmill speed changes (95% CI: 33-89%). Moderate or larger effect sizes were observed for measures of gait performance, balance, fitness, cognition, fatigue, perceived change and brain volume. Participants with baseline comfortable gait speed <0.4 m/s had less absolute improvement in walking capacity but similar proportional and perceived changes. Conclusions: These findings reinforce the potential of locomotor HIIT research for stroke rehabilitation and provide guidance for more definitive studies. Based on the current results, future locomotor HIIT studies should consider including: 1) both overground and treadmill training; 2) measures of cognition, fatigue and brain volume, to complement typical motor & fitness assessment; and 3) baseline gait speed as a covariate.